Amy Chelsea Stacie Dee - Thompson, Mary G. (Mary Gloria), 1978- (G.P. Putnam's, 2016)
"Amy and her cousin Dee were kidnapped six years ago, and when Amy finds her way home, she's desperate to protect the ones she loves at any cost"--